Distribution of human papilloma virus genotypes and treatment outcomes in definitive radiotherapy for cervical cancer. (3rd January 2023) - Kinoshita, Rumiko; Mitamura, Takashi; Kato, Fumi; Hattori, Takahiro; Higaki, Hajime; Takahashi, Shuhei; Fujita, Yoshihiro; Otsuka, Manami; Koizumi, Fuki; Uchinami, Yusuke; Mori, Takashi; Nishioka, Kentaro; et al.
Abstract: Most oncogenic human papilloma virus (HPV) genotypes stratify into two species, α-7 HPV and α-9 HPV. There are several studies that evaluate the relationship between HPV species and treatment outcomes and reports that HPV species is prognostic. The HPV genotyping was conducted using biopsy specimens which had been stored in these studies. We conducted the study using the HPV test performed by cytology specimens which is less invasive and more useful in clinical settings. This study enrolled 46 patients who received HPV genotyping before the definitive radiotherapy. The results of the HPV genotyping were classified into HPVα-7, HPVα-9 and negatives. Of the 46 patients, 10 were positive for HPVα-7, 21 positive for HPVα-9 and 15 were negative. The median follow-up period was 38 months (range 4–142). The HPVα-7, HPVα-9 and negative groups showed the 3-year overall survival (OS; 59.3%, 80.4% and 72.2% [ P  = 0.25]); local control (LC; 67.5%, 81% and 80% [ P  = 0.78]); pelvic control (PC) (50%, 81% and 72.7% [ P  = 0.032]); pelvic lymph node (PLN) control (78.7%, 95% and 92.3% [ P  = 0.012]); distant metastasis free (DMF) survival (50%, 75.4% and 42.8% [ P  = 0.098]); and progression free survival (PFS) rate of patients (30%, 66.7% and 38.9% [ P  = 0.085]), respectively. Patients with HPVα-7 showed statistically significant poorer PC than the HPVα-9 group, in multivariate analysis. This result is consistent with previous studies for HPV positive patients. The HPV negativity rate was higher in this study than in other studies and further work on this may be needed for clinical use.